IMPLEMENTASI KEBIJAKAN PENANGGULANGAN HIV/AIDS OLEH KOMISI PENANGGULANGAN AIDS (KPA) DI KOTA PONTIANAK - Junaidi E.01108077 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This article isthe theme ofHIV/AIDSwhichis intendedtoprovidean understanding of theimplementationprocess ofthe policy implementationof HIV/AIDS. The most fundamentalissuesin this articleisfocusedonthe process ofpolicy implementationof HIV/AIDSbyAIDS Commissionin Pontianakandwhat factorsarecausingtheresponse to HIV/AIDSin thecity ofPontianakhas notsucceeded. Therealachievementofpolicy objectivesorresultsKPAPontianakin tacklingHIV/AIDSisin terms of thecompetence ofthe people themselves, the publicis nowmoreaware of theinformationaboutHIV/AIDSandorpekhaawareof the surroundings, ifneighborsorrelativeswhohave symptoms-symptoms orrisk behaviorregardingHIV/AIDS, toleador at leastprovide inputthattheneighborsorrelativestoimmediatelycheck themselvesin theclinicorat a nearby hospitalrelatedto HIV/AIDS. Keywords:Countermeasures HIV/AIDS, Socialization Danger of HIV/AIDS, Institutional Cooperation